Evaluation of breakage kernels for liquid–liquid systems: Solution of the population balance equation by the least‐squares method. (25th July 2013) - Solsvik, Jannike; Borka, Zsolt; Becker, Per Julian; Sheibat‐Othman, Nida; Jakobsen, Hugo A.
Abstract The breakage frequency and daughter size distribution functions by Coulaloglou and Tavlarides[1] are frequently adopted closures in population balance (PB) modelling. A survey of the extensions and modifications of the Coulaloglou and Tavlarides[1] breakage frequency function is provided. Furthermore, the daughter size distribution functions within the statistical category, herein the model proposed by Coulaloglou and Tavlarides[1], are outlined. Most of the breakage models available in literature commonly assume binary breakage only. Thus, the daughter size distribution function suggested by Diemer and Olson[2] is of interest as higher order breakage can be modelled. The breakage closures are evaluated solving the population balance equation (PBE) for a liquid–liquid emulsification system in a stirred tank. The results obtained from a least‐squares solver are compared with the experimental data when available.